EFEKTIVITAS PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP APARAT DESA LOLOFITU KECAMATAN LOLOFITU MOI KABUPATEN NIAS BARAT - Erwin Jaya Waruwu , Hervis; Ndraha, Ayler Beniah; Laia, Otanius; Harefa, Peringatan (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This research is motivated by the problems faced by Lolofitu Village officials regarding the use of information technology which is still not optimal. This research aims to find out how information technology is used by Lolofitu Village officials, supporting and inhibiting factors in the use of information technology by Lolofitu Village officials and efforts to use it. information technology for Lolofitu Village officials. This research uses qualitative methods to gain an in-depth understanding of the phenomena related to the effectiveness of the use of information technology for Lolofitu Village officials. The results of this research show that the Lolofitu village office faces a number of challenges in the use of information technology, including lack of adequate infrastructure, limited resources and low knowledge and ability of village officials in operating information technology.